STUDENTS’ ATTITUDES TOWARD ONLINE-INSTRUCTION AT FACULTY OF EDUCATION SOUPHANOUVONG UNIVERSITY, ACADEMIC YEAR 2019-2020 - XANG , Yang; KHOTSAIGNOH , Saiphone; SOULIVONG, Phetsamone; Sidaphone, Soulinthone; phatuomvanh, Phanthamanath; PHALIBAY, Bounthiem (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
This research intended to investigate on Students’ Attitudes toward Online-instruction at Faculty of Education Souphanouvong University during the pandemic of COVID-19, The research aimed to investigate the student`s opinion about the Online instruction and compare mean with a variables of Urban-resident students and Rural-resident students. 165 students were selected as samples from the total of 283 students who are currently studying in the Faculty of Education, the instrument used was a questionnaire with five rating scales. Prior to using the questionnaire, it was tested by the IOC = 1 and reliability of .964 the data was analyzed by comparing the Mean and Standard Deviation of the two student groups. The research findings found that: The students’ attitude toward online-instruction at the Faculty of Education was of a medium level by the mean of = 3.35 and = 1.05 The students from different residence have different opinions toward online-instruction with the statistical significant of .05